PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK MINYAK GORENG TAWON DI TOKO ADIT BALIKPAPAN - Febrianti, Sinta; C. Prihandoyo, C. Prihandoyo; Dedy Deomedes, Stepanus (Fakultas Ekonomi Universitas Balikpapan, 2024)
This research aims to analyze the partial and simultaneous influence of marketing mix variables (product, price, location and promotion) on purchasing decisions for cooking oil products “Tawon” on Adit Shop Balikpapan. The type of research used is quantitative research. The number of samples in this study was 323 final consumers and not retail shop entrepreneurs who bought cooking oil “Tawon” for resale. The sampling technique used in this research is non-probability sampling with purposive sampling. The data analysis used is descriptive analysis and multiple linear regression analysis. The test tools used are instrument testing, classical assumption testing, and hypothesis testing. The results of multiple linear regression analysis show that product, price, location and promotion variables have a positive and significant influence on purchasing decisions, either partially or simultaneously. The price variable has the most dominant influence on purchasing decisions for Tawon cooking oil products at the Adit Shop Balikpapan.